Critical Success Factors in Implementing Employee Information System BasedOn E-Government in The Bureau of Public Affairs at The Regional SecretariatOf West Java Province - Dea Melati; Entang Adhy Muhtar; Elisa Susanti (Jurnal Manajemen Pelayanan Publik, 2020)
This research aimed to identify critical success factors in the implementation of EGovernment based on employee management information system in the Bureau of Public Affairs at the Regional Secretariat of West Java Province. Employee management information system is a process on managing information through the use of available resources within the organization. The formulation of the problem in this study is in its implementation in which various kinds of obstacles were found such as the difficulties in operating digital-based information system applications by each employee, also the inaccuracy of available data in information system. Qualitative method was used in this research by collecting data through literature review study, field research and interviewing four informants. They were the Head of the Public Affairs Bureau at the Regional Secretariat of West Java Province, the Head of Household Administration and Staffing, the administrator staff for management information system and a civil servant within the General Affairs Bureau. The research shows that the implementation of employee management information system based on e-government in the Bureau of Public Affairs at the Regional Secretariat of West Java province is not optimal because it has not been supported by competent human resources in the implementation of technology-based management information system therefore data accuracy is difficult to be achieved.